Live attenuated influenza A virus vaccines with modified NS1 proteins for veterinary use - Nogales, Aitor; DeDiego, Marta L.; Martínez-Sobrido, Luis (Frontiers in Cellular and Infection Microbiology, 2022)
Influenza A viruses (IAV) spread rapidly and can infect a broad range of avian or mammalian species, having a tremendous impact in human and animal health and the global economy. IAV have evolved to develop efficient mechanisms to counteract innate immune responses, the first host mechanism that restricts IAV infection and replication. One key player in this fight against host-induced innate immune responses is the IAV non-structural 1 (NS1) protein that modulates antiviral responses and virus pathogenicity during infection. In the last decades, the implementation of reverse genetics approaches has allowed to modify the viral genome to design recombinant IAV, providing researchers a powerful platform to develop effective vaccine strategies. Among them, different levels of truncation or deletion of the NS1 protein of multiple IAV strains has resulted in attenuated viruses able to induce robust innate and adaptive immune responses, and high levels of protection against wild-type (WT) forms of IAV in multiple animal species and humans. Moreover, this strategy allows the development of novel assays to distinguish between vaccinated and/or infected animals, also known as Differentiating Infected from Vaccinated Animals (DIVA) strategy. In this review, we briefly discuss the potential of NS1 deficient or truncated IAV as safe, immunogenic and protective live-attenuated influenza vaccines (LAIV) to prevent disease caused by this important animal and human pathogen.